2008
DOI: 10.1103/physrevb.77.184301
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence by a spin thermal bath: Role of spin-spin interactions and initial state of the bath

Abstract: We study the decoherence of two coupled spins that interact with a spin-bath environment. It is shown that the connectivity and the coupling strength between the spins in the environment are of crucial importance for the decoherence of the central system. For the anisotropic spin-bath, changing the connectivity or coupling strenghts changes the decoherence of the central system from Gaussian to exponential decay law. The initial state of the environment is shown to affect the decoherence process in a qualitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…Furthermore I investigate only the case where all couplings are isotropic, i.e. Therefore, the decoherence process is solely determined by the interactionĤ I which makes a discussion of Ω needless [293] (in all simulations Ω = −1).…”
Section: Few Qubits In a General Spin Bathmentioning
confidence: 99%
“…Furthermore I investigate only the case where all couplings are isotropic, i.e. Therefore, the decoherence process is solely determined by the interactionĤ I which makes a discussion of Ω needless [293] (in all simulations Ω = −1).…”
Section: Few Qubits In a General Spin Bathmentioning
confidence: 99%
“…In this work we construct a model where we can continuously tune the degree of frustration in the environment by a single parameter κ, confirming that frustrated environments reduce the coherence of the central spin much more efficiently compared to an environment with a low degree of frustration, as previously found in Refs. [16,17]. Using this model we study the structure of the eigenvalues of the Hamiltonian of the environment, H E , in the presence of a central spin.…”
Section: Introductionmentioning
confidence: 98%
“…In Refs. [16,17], decoherence of a two-spin system was studied, and a large enhancement of decoherence was found for frustrated spin environments, the main conclusion being "For the models under consideration, the efficiency of the decoherence decreases drastically in the following order: spin glass, frustrated antiferromagnet, bipartite antiferromagnet, one-dimensional ring with nearest-neighbor antiferromagnetic interactions" [16]. A similar study found that the same was true also with regards to relaxation towards the ground state of the central system.…”
Section: Introductionmentioning
confidence: 98%
“…Even in the case of numerical diagonalization, for instance, a system of 32-42 ( 1 2 )-spins requires 128 GB-32 TB of local memory which is beyond the capacity for most computers in the world, in the best case. Nevertheless, multiples approaches to such dimensional problem, which imply basic many-body techniques reaching successful results through a generalization of the behavior of a single spin-architecture, have been proposed [14,[28][29][30]. The advantage of these and other approaches, from point of view of realistic computations is clear: It is easier to handle large matrices and their components in an algebraic way, than numerically diagonalize a large matrix.…”
Section: Energy Spectrum and Excitation Frequenciesmentioning
confidence: 99%